Development Of A Pulsed Launcher System - Mohamed, Mohd Rezal (2007)

(untitled)
Launcher is a device used to launch a projectile. Launcher requires energy to operate and it could be air pressure, compress spring, chemical or electromagnetic energy. Normal launcher applies an explosive to launch a projectile like rocket and bullet. It produces a loud sound, smoke and fire when the explosion occurred. This will shorten the lifetime of barrel and launch pad when the explosion erodes it. Thus to overcome this problem, a launcher is design to launch a projectile without producing a loud sound, explosion and fire. A pulsed launcher system is design using single coil with complete switching circuit, projectile, control circuit, and capacitor bank. The purpose in designing this launcher is to launch a projectile and obtaining the highest projectile speed of designed launcher with correct value of capacitor bank and projectile position. Experiments and simulations are done to identify the relationship between voltage, capacitance, and projectile initial position. Results are obtained by collecting data and tabulated in graphs. Based on the results it found that the coil current increase when the voltage and capacitance of the capacitor bank is increases and vice versa. The projectile speed is decreasing when the projectile initial position is more than half of the coil length. The position of the projectile with a correct value of capacitor bank is obtained for the designed launcher to operate with highest projectile speed. In this research, a 16 mH coil give a highest projectile speed of 23.07 ms-1 (horizontal motion) and 11.62 ms-1 (vertical motion) when the coil is supply with 680.2 V, 286 uF capacitor bank at 1 cm projectile initial position inside the coil. The energy conversion from electric energy to kinetic energy is low, 10.05 % for horizontal motion and 2.55 % for vertical motion. The launcher requires more energy to launch the projectile at vertical motion to overcome the gravitational force.